2007
DOI: 10.1016/j.visres.2006.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Direction and extent of perceived motion smear during pursuit eye movement

Abstract: Smooth pursuit eye movements superimpose additional motion on the retinal image of untracked visual targets, potentially leading to the perception of motion smear and a distortion of the perceived direction of motion. Previously, we demonstrated an attenuation of perceived motion smear when the untracked target moves in the opposite direction of an ongoing pursuit eye movement. In this study, the extent of perceived motion smear and the direction of perceived smear were compared for a single bright dot that mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 50 publications
5
22
0
Order By: Relevance
“…This in turn means that motion opposite to the pursuit direction is selectively attenuated, leaving other directions unaffected. A similar pattern has been shown for perceived motion smear during pursuit (Bedell & Lott, 1996;Geisler, 1999;Tong, Aydin, & Bedell, 2007;Tong, Patel, & Bedell, 2005). These studies obtained that pursuit attenuates the perceived motion smear only for motion in the opposite direction, leaving motion in orthogonal direction unaffected.…”
Section: Comparison To Earlier Studiessupporting
confidence: 78%
“…This in turn means that motion opposite to the pursuit direction is selectively attenuated, leaving other directions unaffected. A similar pattern has been shown for perceived motion smear during pursuit (Bedell & Lott, 1996;Geisler, 1999;Tong, Aydin, & Bedell, 2007;Tong, Patel, & Bedell, 2005). These studies obtained that pursuit attenuates the perceived motion smear only for motion in the opposite direction, leaving motion in orthogonal direction unaffected.…”
Section: Comparison To Earlier Studiessupporting
confidence: 78%
“…Furthermore, in agreement with a previous finding that the reduction of subjective motion blur during pursuit is direction selective [15], [16], we also found the temporal resolution improvement during pursuit was direction selective. In this experiment, while the observer was making a pursuit, we presented the bars moving at a display speed twice as fast as the pursuit target (Figure 4 D).…”
Section: Resultssupporting
confidence: 93%
“…This motion deblur enhancement was only observed when the untracked target moved in the opposite direction of pursuit [15], [16]. Given that the motion deblur implies a reduction in signal mixture among spatially adjacent inputs, its enhancement during pursuit is consistent with our finding of increased temporal resolution.…”
Section: Discussionsupporting
confidence: 88%
“…Another effect, which might be related to the temporal changes of luminance processing, is the selectively reduced extent of perceived motion smear during smooth pursuit for motion in the opposite direction (Bedell & Lott, 1996;Tong et al, 2005Tong et al, , 2007. As such, a suppression of motion smear also occurs during passive eye movements, and it has been concluded that the effect is at least partially caused by proprioceptive signals .…”
Section: Discussionmentioning
confidence: 99%